(untitled) (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: This study investigates how religion affects student dress at Ghanaian universities, particularly at Accra Technical University (ATU) and Kumasi Technical University (KsTU). It looks into how students’ wardrobe choices are influenced by their religious convictions in light of the rising prevalence of indecent attire among college students. Design/Methodology/Approach: A quantitative survey used a structured questionnaire to collect student data, and 304 respondents answered the questionnaire. The data were analysed using descriptive statistics from the Statistical Package for the Social Sciences (SPSS). The study examined the relationship between students’ religious beliefs and clothing codes at various colleges. Findings: The findings show that religious convictions significantly impact what students wear to Ghanaian universities. The study emphasises the necessity of dress code regulations and policies that consider these factors and encourage students to behave appropriately. Research Limitation: This study examines two institutions and offers important insights into the viewpoints of Ghanaian universities. Hence the findings cannot be generalised. Social Implication: The results highlight how crucial it is to consider religious views when debating student dress standards, arguing that they should uphold decency while honouring cultural and religious values. Practical Implication: According to the survey, college religious communities should be consulted when creating dress code policies. To address concerns about indecent dress, these rules should explicitly outline what is appropriate for different circumstances, including public spaces and classrooms. Originality/Value: This study advances knowledge of how religion influences Ghanaian students’ fashion choices. It offers insightful information for legislators and educational establishments seeking to establish welcoming and courteous spaces considering their student groups’ cultural and religious backgrounds.